PENGARUH SOCIAL SUPPORT TERHADAP HOMESICKNESS PADA MAHASISWA RANTAU ASAL KEPULAUAN MENTAWAI - Oktarisna Waruwu, Lilis; Rinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of social support on homesickness among migrant students from the Mentawai Islands studying in West Sumatra. A quantitative approach with simple linear regression was employed, involving 163 participants selected through purposive sampling. The study used the Social Support Scale based on Sarafino and Smith (2011) and the Homesickness Scale based on Archer et al. (1998). Data were analyzed using JASP. The results indicated that social support had a significant effect on homesickness (t = 3.094, p = 0.002, R = 0.237, R² = 0.056), explaining 5.6% of the variance in homesickness, while the remaining 94.4% was influenced by other factors outside the scope of this study. The findings suggest that higher levels of social support are associated with lower levels of homesickness, indicating that social support serves as an important protective factor in helping migrant students adapt to a new environment.